Phase diagram of the B–B₂O₃ system at pressures to 24 GPa - Turkevich, V.Z.; Turkevich, D.V.; Solozhenko, V.L. (Сверхтвердые материалы, 2016)
The evolution of topology of the B–B₂O₃ phase diagram has been studied at pressures up to 24 GPa using models of phenomenological thermodynamics with interaction parameters derived from experimental data on phase equilibria at high pressures and high temperatures. Вивчено еволюцію топології фазового діаграми B–B₂O₃ при тисках до 24 ГПа з використанням моделей феноменологічної термодинаміки з параметрами взаємодії, отриманими з експериментальних даних про фазову рівновагу при високих тисках і високих температурах. Изучена эволюция топологии фазового диаграммы B–B₂O₃ при давлениях до 24 ГПа с использованием моделей феноменологической термодинамики с параметрами взаимодействия, полученными из экспериментальных данных о фазовом равновесии при высоких давлениях и высоких температурах.